A rhodamine-based chemosensor and functionalized gel ball for detecting and adsorbing copper ions. (29th January 2021) - Yang, Liu; Zhang, Xiaoxue; Yang, Jiao; Yuan, Mao-Sen; Wang, Jinyi
Abstract: The development of sensitive colorimetric and fluorescent chemosensors for Cu 2+ sensing has gained much attention in recent years because of their potential application in clinical biochemistry and environmental studies. Herein, a novel rhodamine-based chemosensor NRG was constructed, which exhibited high sensitivity and selectivity and a quick response for Cu 2+, accompanied by remarkable color and fluorescence changes. Moreover, besides sensing Cu 2+, NRG can capture Cu 2+ effectively and quickly in aqueous solution. Based on the results, NRG -functionalized gel balls were fabricated and exhibited strong adsorbability and a high adsorption capacity for Cu 2+, accompanied by an obvious color change. More interestingly, the gel balls can be recycled after treatment with an EDTA solution. These excellent properties make the gel ball a promising candidate for copper ion purification. Graphical abstract: Image 1